PEMBERDAYAAN DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA DI KABUPATEN OGAN ILIR PROVINSI SUMATERA SELATAN - Milsani Ramkita; Basron Anadoyya; Alya Syafitri Lubis; Rahmat Hidayat (Al-Mubin, 2026)
This study aims to analyze the influence of community empowerment on participation in village development in Ogan Ilir Regency, South Sumatra Province. The research used a survey approach involving 270 respondents from 11 districts, analyzed through structural path analysis and qualitative descriptive techniques. The results show that community empowerment has a significant impact on community participation in village development. The dimension of creating a conducive environment has the strongest influence, followed by capacity building, while community protection has the weakest effect. In conclusion, community empowerment plays a crucial role in enhancing community involvement and independence toward sustainable rural development.